Theological Thinking Abû al-Ḥasan ‘Alî al-Hasani al-Nadwî - Sori Monang (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The aims of this study to find out the theological Thinking Abû al-Ḥasan ‘Alî al-Hasani al-Nadwî. The result in this study shows that Al-Nadwî is a great Ulama with a very complex socio-cultural background, born during the colonial era and struggling in a period of development transition and national change that makes al-Nadwî rich in various experiences of obstacles, be they social, cultural, or religious obstacles. Therefore it is not surprising that al-Nadwî grew up as a Fundamentalist Ulama. He is a Ulama figure who is active in defending religion both in literature and in terms of the concept of civilization. Therefore also, he is well aware of the potential of Muslims and also the various problems that surround him from time to time.. Al-Nadwî, if seen in him as a figure of a fundamentalist cleric, then in line with this is the thought and movement that he should be seen real. Among al-Nadwi's awareness as a modern-day ulema of modern reform is his maturity in analyzing the present condition of the Muslims with a comparative study of Western existence. According to al-Nadwi, the decline of Islam is based on two things, first; because Muslims have abandoned their religion; Second, because Muslims do not master science. According to al-Nadwî, these two things are sources of strength that are not separated from each other.